Setting up learning opportunities to teach social skills - Gerður Sif Heiðberg 1999- (2022)
The adjustment from kindergarten to elementary school may be challenging, particularly for children who lack school readiness. Teaching children to respond to their name-calls, make eye contact, and to answer has been founded to increase compliance with specific instructions. The Preschool Life Skills (PLS) program was first established as a class-wide teaching program for regularly growing preschool children, and it teaches instruction following, functional communication, delay tolerance, and friendship skills. These abilities were selected for class-wide teaching as they were identified by educators as crucial for primary school achievement. The purpose of the current study was to examine if teachers who implement the PLS program set up more learning opportunities for children throughout the day, compared to teachers that do not implement the PLS program. PLS was implemented in kindergarten in Iceland for children entering first grade in elementary school. The participants were 13 teachers and two of them implemented PLS. Data was collected for every minute in thirty-minute observation sessions. Results showed that the PLS program did not increase learning opportunities throughout the day. The change in the test group which went through the PLS program was not significantly different from the change in the control group. Keywords: Preschool Life Skills, social skills, kindergarten, teacher, children, instruction Aðlögun frá leikskóla yfir í grunnskóla getur verið krefjandi, sérstaklega fyrir börn sem skortir skólaundirbúningsgetu. Þegar börnum var kennt að svara nafnaköllum sínum, halda augnsambandi og þau svöruðu gat það aukið viðbrögð við ákveðnum fyrirmælum. The Preschool Life Skills (PLS) var fyrst sett fram sem bekkjarkennsluáætlun fyrir eðlilega þroskuð leikskólabörn og kennir fræðslu, virk samskipti, seinkun umburðarlyndis og vináttufærni. Þessir hæfileikar voru valdir af kennurum fyrir bekkjakennslu þar sem þeir skipta sköpum fyrir árangur í grunnskóla. Tilgangurinn með rannsókninni var að skoða ...